SSR ANALYSIS IN THE STUDY OF GENETIC DIVERSITY AND SIMILARITY OF BARLEY CULTIVARS - O. R. Lakhneko; B. V. Morgun; R. M. Kalendar; A. I. Stepanenko; A. V. Troianovska; O. I. Rybalka (Biotechnologia Acta, 2016)
The aim of research was to develop an evaluation system of the genetic polymorphism for barley cultivars of Ukrainian and foreign origin based on the analysis of simple sequence repeats and valuable agricultural trait loci as well as to compose the molecular genetic passports for those cultivars. PCRs with the following separation of amplification products by agarose and polyacrylamide electrophoresis were performed to find out genetic polymorphism. Unweighted Pair Group Method with Arithmetic Mean was used for phylogenetic relationship detection. The dandrogram of phylogenetic relationships of 55 barley cultivars was constructed and molecular genetic passports were developed. Molecular genetic passports can be involved in verification for the compliance with standards cultivars, stability and seed purity.